2021
DOI: 10.1016/j.heliyon.2021.e05937
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviors and suicide risk among Bangladeshi people during the COVID-19 pandemic: An online cross-sectional survey

Abstract: Background: Suicide, a major public health concern, is a leading cause of injury and death worldwide. The present study aims to assess suicidal behaviors and suicide risk among Bangladeshi people during COVID-19. Methods: A cross-sectional online survey was conducted from July 10 to July 20, 2020, involving 1,415 Bangladeshi residents ages 18 years or older. Data was collected via an anonymous online questionnaire. The Suicide Behaviors Questionnaire-Revised was used to assess suicide risk. The depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
51
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 42 publications
(49 reference statements)
9
51
0
7
Order By: Relevance
“… 21 But compared to the unmarried participants, either divorced or widows or widowers were found being at 6.369 folds of suicidality risk in another study. 24 Similarly, a lower level of education was reported increasing the risk of suicidal ideation; that is, 2.694 and 1.690 times higher risk was found for the education levels of secondary or below, and higher secondary/diploma, respectively; than the graduate or higher as education level. 24 Mamun et al 21 reported that suicidal ideation risk increased in a commensurate manner with the residence of the village to district and divisional cities.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“… 21 But compared to the unmarried participants, either divorced or widows or widowers were found being at 6.369 folds of suicidality risk in another study. 24 Similarly, a lower level of education was reported increasing the risk of suicidal ideation; that is, 2.694 and 1.690 times higher risk was found for the education levels of secondary or below, and higher secondary/diploma, respectively; than the graduate or higher as education level. 24 Mamun et al 21 reported that suicidal ideation risk increased in a commensurate manner with the residence of the village to district and divisional cities.…”
Section: Resultsmentioning
confidence: 94%
“… 24 Similarly, a lower level of education was reported increasing the risk of suicidal ideation; that is, 2.694 and 1.690 times higher risk was found for the education levels of secondary or below, and higher secondary/diploma, respectively; than the graduate or higher as education level. 24 Mamun et al 21 reported that suicidal ideation risk increased in a commensurate manner with the residence of the village to district and divisional cities. In contrast, another study observed that 2.34-times higher risk of suicidal ideation among the urban participants compared to rural ones.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations